Adaptation or Degradation: What’s Happen to Educational Innovation in a Typical Educational Process? - A. P. Isaev; L. V. Plotnikov (Высшее образование в России, 2023)
The article is devoted to the study of the processes of changing innovative learning technology in the conditions of a typical educational process. The study was conducted on the example of end-to-end design technology (based on the CDIO methodology in accordance with its standards) for bachelor’s degree in technical areas of training. The study used methods of expert assessment, written survey, content analysis, structural-logical and statistical analysis. The experts were engineers of design departments of industrial enterprises, teachers of engineering disciplines of the university and undergraduate students. A review analysis of the understanding of educational innovation available in the scientific literature is carried out. A concise description of the end-to-end design technology for a training and production workshop that meets the criteria of educational innovation is presented. Based on the expert assessment, a detailed analysis of the influence of the conditions of the typical educational process of the university on the change of the specified learning technology at the level of the characteristics of students’ academic work and its results is made. Data on changes in innovative technology according to the criteria of twelve CDIO standards, as well as its impact on the formation of hard and soft skills of engineers before and after adaptation are presented. A comparative analysis of the assessments of changes in teaching technology made by students and experts is carried out, on the basis of which conclusions are substantiated about: 1) the nature of the degradation of educational innovation when it is introduced into the standard learning process; 2) the special role of the first stages of end-to-end design technology for the formation of effective skills of educational and practical work, which partially compensate for the shortcomings of the educational process caused by its adaptation to the conditions of a typical university education. A hypothesis is also put forward about the reasons for the low efficiency of educational innovations in the educational process of universities.